Avaliação da influência de parâmetros físicos e químicos na precipitação de carbonatos por bactérias haloalcalófilas e comparação com descrições carbonáticas do Pré-sal - Lopes, Caroline Zilio (2022)
The saline-alkaline lakes present in the sub-region Nhecolândia, Mato Grosso do Sul (Brazil), harbor microbial species known as haloalkalophiles, as they have the ability to live in conditions of high salinity and alkalinity. For such, adaptability, these species have specific genes and use different metabolic strategies. They may also produce Extracellular Polymeric Substances or EPS that help in their establishment and protection in these environments. Moreover, indirectly, haloalkalophilic species may be involved in biogeochemical processes, being able to act in the dissolution and precipitation of carbonates in these sites. In this context, this work sought to investigate the influence of different physical and chemical on calcium carbonate precipitation performed by 24 haloalkalophilic bacteria isolated from three saline-alkaline lakes of Brazilian Pantanal. Mineral precipitates formed by microorganisms in medium for carbonate precipitation (MPC) under different conditions were morphologically evaluated and selected for Scanning Electron Microscopy (SEM) and X-Ray Diffraction (XRD) analysis. Among the isolates selected according to the morphology of the formed precipitates, six were taxonomically identified as belonging to the bacterial genus Halomonas. Of these, three distinct isolates were selected and cultured again for evaluation of CFU/mL, presence and quantification of eventually formed EPS and wet and dry weight. A co-culture with these three isolates was also carried out and their precipitates evaluated. In addition, mineral precipitates formed in individual inocula in MPC containing the isolates previously autoclaved were also evaluated. In order to evaluate the role of EPS in the precipitation process, they were chemically characterized, isolated from microorganisms and inoculated into MPC. Also, petrographic slides of mineral precipitates selected after SEM and XRD analyzes were compared to carbonate formations of different Pre-salt strata described in the literature. Finally, a review manuscript covering the topic biofilms in nature was developed in order to promote a better understanding of the topic in different areas of knowledge.